ChemInform Abstract: Transition‐Metal‐Doped Zinc Oxide Nanoparticles as a New Lithium‐Ion Anode Material. Issue 10 (11th March 2014) - Bresser, Dominic; Mueller, Franziska; Fiedler, Martin; Krueger, Steffen; Kloepsch, Richard; Baither, Dietmar; Winter, Martin; Paillard, Elie; Passerini, Stefano
Abstract Zn0.9Fe0.1O (I) and Zn0.9Co0.1O (II) nanoparticles are prepared from their respective aqueous gluconate hydrates in a sucrose solution followed by H2O evaporation, drying at 300 °C, and calcination in air (450 °C, 3 h).